2009
DOI: 10.1111/j.1365-2214.2008.00919.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Turkish children and adolescents: prevalence and non‐nutritional correlates in an urban sample

Abstract: In the present study, we focused on some of the non-nutritional correlates of obesity in a representative population of an urban area in a developing country. Obesity prevalence rate in Turkish children living in Aydin was higher in children from a higher socio-economic group in contrast to reports from many developed countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
28
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 28 publications
9
28
1
1
Order By: Relevance
“…Obesity rate observed in this study was much lower than the rates reported in recent literature from various non-Chinese adolescent populations [29][30][31] and the rates reported in a national survey of Chinese cities in children aged 7 to 18 years in 2000. 20 As we used the same criterion to define obesity as the Chinese national survey, the lower rate observed in our study could not be explained by differences in definition.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Obesity rate observed in this study was much lower than the rates reported in recent literature from various non-Chinese adolescent populations [29][30][31] and the rates reported in a national survey of Chinese cities in children aged 7 to 18 years in 2000. 20 As we used the same criterion to define obesity as the Chinese national survey, the lower rate observed in our study could not be explained by differences in definition.…”
Section: Discussioncontrasting
confidence: 77%
“…Higher obesity rates in boys than in girls have also been reported in countries outside China, 29,30 but not in other studies. 31,41,42 Cultural and life-style factors during early childhood and adolescence could be the explanations for the differences in sex-obesity relationship reported in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors such as change in lifestyles and diet, urbanization, lack of adequate physical activity and devoting greater time to sedentary activities like television viewing and playing on a computer should be considered as major causes of overweight/obesity in various countries (8,11,(20)(21)(22)(23) . Although a number of factors associated with obesity in children and adolescents seem to be similar in various countries, nevertheless the distribution of these factors and their contribution to the development of childhood obesity may be different across different populations (8,17,18,20,24) . With regard to the subsequent socio-economic public health burden of childhood obesity (6,7) , these observations emphasize the need for preventive measures to control overweight and obesity at earlier stages of life.…”
mentioning
confidence: 99%
“…Similarly, in other geographic regions such as the Middle East countries including Iran, the prevalence of obesity in children is also rising. Recent reports indicate that over 15 % of children living in Iran and neighbouring countries are overweight or obese (5,(16)(17)(18)(19) . The high prevalence rate of overweight/ obesity among children in northern Iran is of particular concern and worries families into seeking weight-reduction programmes (19) .…”
mentioning
confidence: 99%
“…4 Re cent stu di es ha ve de mons tra ted that, the pre va len ce of over we ight and obe sity we re 10.3-21.8% and 1.6-6.1%, res pec ti vely, in Tur key. [5][6][7] Early di ag no sis of obe sity, which is de fi ned as a chro nic di se a se, es pe ci ally in child ho od, and prompt tre at ment ini ti a ted by ta king the re qu i red me a su res are im por tant for the pre ven ti on of comp li ca ti ons in child ho od and adult ho od. 4,8 In re cent ye ars an in cre a se in body fat mass and musc le tis su e in child ho od and ado les cen ce has be en ac com pa ni ed by an in cre a se in he ight.…”
mentioning
confidence: 99%